The novel influenza a (H1N1) infection in infants and children (Bangladesh Journal of Medical Science, 2010)
During the 1918 Spanish Flu pandemic, often described as the most devastating epidemic in recorded history, 1 in 5 person was infected and an estimated 50 million lives were lost. The disease was so widespread and pervasive that even the children had a tune which they skipped rope to: I had a little bird, its name was Enza, I opened the window and In-Flu-Enza. DOI: 10.3329/bjms.v8i4.4705 Bangladesh Journal of Medical Sciences Vol.8(4); October 2009 pp84-90